Uma perspectiva da modelagem QSPR para triagem/desenho de catalisadores para a síntese de carbonatos oleoquímicos - Santos, Victor Hugo Jacks Mendes dos (2018)
To date, only a small number of organocatalysts have been applied to produce oleochemical carbonates, while the description of new catalysts system still limited. This work presents a preliminary perspective of Quantitative Structure-Property Relationship (QSPR) modeling to assist in the targeted choice/design of active organocatalysts to produce cyclic carbonates. The QSPR was developed by applying the molecular descriptors (2D) to model the structure-property relationship between the organocatalysts features and its activity to produce oleochemical carbonates. From the virtual screening, a total of 122 catalysts have their activity predicted and the best molecular targets are proposed. The principal molecular features (organic structure, molecular arrangement, carbon chain size and substituent type) were identified through data mining, while the principal component analysis (PCA) proved to be suitable to perform the exploratory analysis of the molecules set. In addition, is presented the first report of the application of cetyltrimethylammonium bromide (CTAB) as a new catalyst to produce oleochemical carbonate derived from soy, canola and rice oils. The reactions were performed in a 50 cm3 stainless steel autoclave at 120°C, for 48 hours, without stirring, 5 MPa (p, CO2), 2 g of epoxidized oil, 4 mL of butanol and 5 mol% of CTAB. From the proposed method, all reactions showed more than 98% of epoxide conversion to cyclic carbonate for all the vegetable oil. In this way, the QSPR modelling can be applied to reduce the costs and time in the organocatalysts screening/design for the cyclic carbonates synthesis from CO2 and epoxides.